Clinical profile, etiology, type and outcome of neonatal seizures: a hospital-based study - Chesti, Mohmad Saleem; Shahzad, Naveed; Chaman, Shilakha; Gazala, Sheenam (International Journal of Contemporary Pediatrics, 2021)
Background: Our study was undertaken to study the etiological factor, clinical profile, types and outcome of newborn with neonatal seizures (NNS). Methods: Our study was hospital based prospective study was done in Sheri Kashmir institute of medical sciences (SKIMS) Bemina from April 2013 to April 2015 in NICU, after obtaining ethical clearance from institutional ethical committee. All neonates fulfilling inclusion criteria were included in our study. Results: In our study, 80 neonates with seizures were included in our study, among them 48 were males and 32 were females. Majority of neonates (57.5%) developed seizures during first 72 hours of life due to birth asphyxia. Commonest types of neonatal seizures observed in our study were subtle observed in 46 cases, followed by tonic (21.2 %), clonic (14.9 %) and mixed (6.2%) seizures. Birth asphyxia was commonest cause (57.5%) of NNS, sepsis with meningitis (18.7%) followed by hypoglycemia (13.7%) and hypocalcemia (5%). Cases of birth asphyxia were associated with higher mortality (58.3%) as compared to cases with metabolic seizures. Conclusions: From our study we conclude that commonest cause of neonatal seizure was birth asphyxia occurring within 72 hours of birth. Sepsis and meningitis were also common infections resulting in neonatal seizure, while as hypoglycaemia and hypocalcemia were common biochemical abnormalities leading to NNS. Early identification and treatment are likely important for long-term outcomes in acute symptomatic seizure.